2018
DOI: 10.1021/acsnano.8b00477
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Boronic Ester Modified Dextran Polymer Nanoparticles as Reactive Oxygen Species Responsive Nanocarrier for Ischemic Stroke Treatment

Abstract: Ischemic stroke is a leading cause of long-term disability and death worldwide. Current drug delivery vehicles for the treatment of ischemic stroke are less than satisfactory, in large part due to their short circulation lives, lack of specific targeting to the ischemic site, and poor controllability of drug release. In light of the upregulation of reactive oxygen species (ROS) in the ischemic neuron, we herein developed a bioengineered ROS-responsive nanocarrier for stroke-specific delivery of a neuroprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
184
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(185 citation statements)
references
References 44 publications
1
184
0
Order By: Relevance
“…This may utilize targeting moieties that specifically target the BBB and/or the infarcted area. In view of this, several peptides have been proposed in the literature that targets the endothelial cells of the BBB (e.g., angiopep‐2), the infarcted tissue (e.g., stroke homing peptide), or cell‐penetrating peptides45d that have the ability to enhance the uptake of the bearing nanostructures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may utilize targeting moieties that specifically target the BBB and/or the infarcted area. In view of this, several peptides have been proposed in the literature that targets the endothelial cells of the BBB (e.g., angiopep‐2), the infarcted tissue (e.g., stroke homing peptide), or cell‐penetrating peptides45d that have the ability to enhance the uptake of the bearing nanostructures.…”
Section: Discussionmentioning
confidence: 99%
“…Other combinational approaches made use of glycan‐based nanostructures such as chitosan and dextran, that were respectively loaded with growth factors and apoptosis inhibitors (Z‐Asp(OMe)‐Glu(OMe)‐(OMe)‐fluoro methyl ketone (Z‐DEVD‐FMK)), as well as neuroprotectants, as the previously mentioned NR2B9C peptide . Surface functionalization was also performed using antibodies against the transferrin receptor or peptides such as the stroke homing peptide (SHp) . It has to be noted that some of these nanotherapeutics were designed in a way to respond to factors that are characterizing ischemic stroke conditions, such as the overproduction of thrombin, MMP‐9,86b and ROS .…”
Section: Combinational Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The system was used for H 2 O 2 ‐activated drug delivery, in which, H 2 O 2 oxidized the copolymer to increase the lower‐critical‐solution temperature to above 37 °C, thus activating drug release. Moreover, Xin and co‐workers reported another H 2 O 2 ‐responsive delivery system for the effective treatment of ischemic stroke. A dextran‐based nanoparticle modified by boronic esters was constructed.…”
Section: Ros‐activated Drug Delivery and Small‐molecular Prodrug Systemsmentioning
confidence: 99%
“…Other teams used red blood cells (RBCs) as a drug delivery carrier. Danielyan et al found that conjugation of t-PA to RBCs prolongs and localizes the activity of t-PA within the bloodstream and used the conjugate as a thromboprophylactic agent referred to as RBC/t-PA. 53) Preinjection of RBC/t-PA brought about rapid lysis of nascent cerebral thrombi, rapid and durable reperfusion, and reduction in morbidity and mortality in a mouse model of cerebral thrombosis caused by injection of preformed fibrin emboli into MCA. Lv et al developed a bioengineered ROS-responsive nanoparticle using RBC membranes which imparts the natural characteristics of RBCs including biocompatibility, immune-evading ability, and long-term circulating ability in the bloodstream to the nanoparticles.…”
Section: Other Nanoparticle Dds For Ischemic Stroke Treatmentmentioning
confidence: 99%